Analisis Praktik Penguman Formil Undang-Undang Terhadap Undang-Undang Dasar 1945 - Tanto Lailam (PRANATA HUKUM, 2011)
The standard to examine formal verification (forinale toetsingrecht) of law against 1945 Constitution in the Constitutional Court, covering : First, Pancasila and Articles of 1945 Constitution. The contrary can be assessed by value Â of Fourth Article of Pancasila and legal substance of Article 5 paragraph (1), Article 20, Article 21, Article 22A of 1945 Constitution. Second, non-1945 constitution, for example is the general principles of law making process (algemene beginselen van behoorlijke wetgeving), the principles to assessed fact of legislation process (example: law making process in House of Representatives of Indonesia). Third, criminal court decisions, the decisions to assessed criminal offense at law making process, for example: corruption, bribery, and others.